2017
DOI: 10.1063/1.5006569
|View full text |Cite
|
Sign up to set email alerts
|

Entropic uncertainty measures for large dimensional hydrogenic systems

Abstract: The entropic moments of the probability density of a quantum system in position and momentum spaces describe not only some fundamental and/or experimentally accessible quantities of the system but also the entropic uncertainty measures of Rényi type, which allow one to find the most relevant mathematical formalizations of the position-momentum Heisenberg's uncertainty principle, the entropic uncertainty relations. It is known that the solution of difficult three-dimensional problems can be very well approximat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 47 publications
2
57
0
Order By: Relevance
“…It is easily shown that in the neighborhood of α = 1/2 the left-hand side of Equation (31), which, as mentioned above, is valid accidentally for any state, behaves as…”
Section: Dirichlet Wellmentioning
confidence: 82%
See 1 more Smart Citation
“…It is easily shown that in the neighborhood of α = 1/2 the left-hand side of Equation (31), which, as mentioned above, is valid accidentally for any state, behaves as…”
Section: Dirichlet Wellmentioning
confidence: 82%
“…Observe also that its left-hand side is a level-independent one. Figure 4 depicts dimensionless left-and right-hand sides of Equation (31), that is, the quantities…”
Section: Dirichlet Wellmentioning
confidence: 99%
“…At first, the radial entropic moments x a r and x b p are calculated using wave functions in Equation 24 and definition in Equation 18, leading to following forms,…”
Section: Circular Statesmentioning
confidence: 99%
“…Extensive theoretical works have been published covering a broad variety of confining potentials. Two prototypical systems receiving maximum attention are harmonic oscillator (in 1D, 2D, 3D, D dimension) and confined hydrogen atom (CHA) inside a spherical enclosure . A CHA within an impenetrable (as well as penetrable) cavity was studied quite vigorously leading to a host of attractive properties—both from physical and mathematical point of view.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation